Lights, camera, middle school! - Holm, Jennifer L; Holm, Matthew (New York Random House, 2017)
"Babymouse joins the school Film Club and writes the greatest cinematic masterpiece of all time! But when the movie gets shown to the entire school, will it be a box office hit or a flop?"--
English stories
1
Keywords: Animals -- Fiction; Humorous stories; Mice -- Fiction; Middle schools -- Fiction; Motion pictures -- Production and direction -- Fiction; Schools -- Fiction